Pengaruh Pemberian Kombinasi Ekstrak Etanol Piper crocatum dan Ekstrak Akuades Elaeocarpus ganitrus pada Kadar Gula Tikus - Lestari, Apriani; Kiromah, Naelaz Zukruf Wakhidatul; Fitriyati, Laeli (Jurnal Kefarmasian Indonesia, 2023)
Diabetes mellitus is a disease characterized by hyperglycemia. Antidiabetic research using natural ingredients has been carried out a lot, one of which is by utilizing red betel leaves and granite leaves. Combining two plants must be done to increase the antihyperglycemic effect and reduce the toxic effects. This study aimed to obtain the most effective dose variations in combinations of plants that are safer and have better results so that they can be used as alternative treatments. The blood sugar levels were measured in vivo on white Wistar rats induced with streptozotocin using a glucometer. The results showed that a single extract of red betel leaf (100 mg/kg BW) and a single extract of granite leaf (100 mg/kg BW) had a percentage decrease in blood sugar levels of 27% and 10%, respectively. While the combination of extracts with a ratio of 100:100, 50:50, 100:50, and 50:100 mg/kg BW has a decrease in blood sugar levels of 50%, 42%, 33%, and 19% after 21 days of observation. The study also showed that the positive control of 0.036 mg glimepiride caused a 36% decrease in sugar levels. Statistical analysis proved that the effect of reducing blood sugar levels on days 0 to 21 differed for each treatment group with a p-value of 0.05. The study concluded that the combination of red betel leaf extract and granite leaf extract was more effective on blood sugar levels than the single extract of each plant in white male Wistar rats. The percentage reduction in blood sugar levels of the combination extract with a dose ratio of 50:50 mg/kg BW and 100:100 mg/kg resulted in better antidiabetic activity than the positive control glimepiride. The combination ratio of 100:100 mg/kg BW extract had the best antidiabetic activity compared to the other extract treatment groups.